Anxiety, sleep habits and executive function during the COVID‑19 pandemic through parents’ perception: a longitudinal study. - Navarro-Soría, Ignasi; Costa-Lopez, Borja; Collado-Valero, Joshua; Juárez-Ruiz-de-Mier, Rocío; Lavigne-Cerván, Rocío (Springer Nature, 2023)
The present study therefore aims to examine trait and state anxiety, sleep habits and executive functioning during 1 year and a half of the COVID-19 pandemic in children and adolescents through the lens of parents. Assessments were conducted at three different times: April 2020 (T1), October 2020 (T2) and October 2021 (T3). The main sample included 953 children and adolescents aged 6 to 18 years, and scales were used to assess anxiety (STAIC), sleep habits (BEARS) and executive functioning (BRIEF-2). The results showed that 6 months after the outbreak of the pandemic, state and trait anxiety, sleep disturbances and executive dysfunctions increased significantly. One and a half year later, trait anxiety and sleep disturbances have been maintained, while state anxiety and executive dysfunction have decreased their scores obtaining scores similar to those of April 2020. In conclusion, there has been a further decrease in children and adolescents’ mental health since the beginning of the pandemic, and it seems to remain at the present time, such as trait anxiety as a part of the personality.
Keywords: Ansiedad; Trastornos de ansiedad en niños; Sueño; Adolescentes - Hábitos de salud; Niños - Sueño; Funciones ejecutivas (Neuropsicología); COVID‑19